2015
DOI: 10.1016/j.mjafi.2015.02.006
|View full text |Cite
|
Sign up to set email alerts
|

HPV vaccine: Current status and future directions

Abstract: Viral like particles (VLP) and hence highly species specific, thermolabile, costly and are purely prophylactic. The quest for a cheaper, thermostable and broad spectrum vaccine has led to many newer prophylactic vaccines. Therapeutic vaccines were born out of the inescapable necessity considering high HPV related morbidity projected in the non HPV naïve population. Therapeutic vaccines would immediately reduce this burden and also help in the management of HPV related cancers alone or as part of combination st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
50
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 28 publications
0
50
0
6
Order By: Relevance
“…The safety of these vaccines is also sufficiently established by these studies. [6][7][8] In spite of knowledge about the association of HPV with cervical cancer and efficacy of HPV based screening and vaccination as an effective modes for primary prevention of carcinoma cervix, the attitude towards cervical cancer screening and HPV vaccines is very poor in many developing countries, including India. 9 Various studies had concluded that lack of appropriate knowledge, negative attitude towards HPV vaccination and screening is one of the most important factor for poor acceptance of these services.…”
Section: Introductionmentioning
confidence: 99%
“…The safety of these vaccines is also sufficiently established by these studies. [6][7][8] In spite of knowledge about the association of HPV with cervical cancer and efficacy of HPV based screening and vaccination as an effective modes for primary prevention of carcinoma cervix, the attitude towards cervical cancer screening and HPV vaccines is very poor in many developing countries, including India. 9 Various studies had concluded that lack of appropriate knowledge, negative attitude towards HPV vaccination and screening is one of the most important factor for poor acceptance of these services.…”
Section: Introductionmentioning
confidence: 99%
“…4 Entre os anos 2000 e 2013 morreram mais de 200 mulheres por ano devido ao CCU (cerca de três em cada 100 000 mulheres), 5 no entanto, este valor poderá representar uma subestimativa, uma vez que alguns casos de CCU são classificados como "tumor maligno do útero, porção não especificada" e não são contabilizados nesta estatística. 5 A infeção pelo HPV é condição necessária na quase totalidade dos casos de CCU, [5][6][7][8][9][10] existindo mais de 100 genótipos do HPV estudados; 90% dos casos de CCU são provocados pelos genótipos de alto risco (oncogénicos) 16,18,45,31,33,52, 58 e 35. 5,[10][11][12][13][14] A infeção pelos genótipos 16 e 18 está na origem da grande maioria dos casos de CCU Revista Científica da Ordem dos Médicos www.actamedicaportuguesa.com Ribeiro JP, et al Eficácia das vacinas contra o HPV nas mulheres com mais de 24 anos na prevenção do CCU, Acta Med Port 2016 Jun;29 (6): [401][402][403][404][405][406][407][408] -mais de 70% dos casos, 5,6,10,[14][15][16][17] enquanto aproximadamente 10% são consequência da infeção pelos genótipos 45 e 31, 15 e os restantes são causados por outros genóti-pos oncogénicos.…”
Section: Introductionunclassified
“…11,18 Todas as mulheres sexualmente ativas estão em risco de contrair infeção por genótipos do HPV oncogénicos, estimando-se que até 80% das mulheres sofram infeção por HPV (genótipos oncogénicos e/ou não-oncogénicos) ao longo da vida, 9,15 sendo que pelo menos 50% serão infetadas dois a cinco anos logo após o início da atividade sexual, permanecendo, contudo, o risco de infeção significativo em idades mais avançadas. 18,19 A maioria das infeções por HPV é transitória, 6,15 ocorrendo resolução espontânea em 90% dos casos após dois anos, 15 que, no entanto, não confere imunidade contra a infeção pelo vírus. 6,9,12,13,15,16 A eficácia das vacinas contra o HPV nas mulheres até aos 25 anos de idade está bem comprovada, 10,11,16,17,19 porém, a eficácia em idades superiores ainda não está totalmente estabelecida e existem dúvidas quanto à sua utilização.…”
Section: Introductionunclassified
See 2 more Smart Citations